Enhancing waste to hydrogen production through biomass feedstock blending: A techno-economic-environmental evaluation. (15th May 2020) - AlNouss, Ahmed; McKay, Gordon; Al-Ansari, Tareq
Highlights: Hydrogen rich syngas can be produced from gasified waste biomass. Optimum feedstock blending options are utilised to maximise hydrogen production. A hybrid environmental and economic optimisation methodology is implemented. Steam gasification demonstrates excellence in providing hydrogen-rich syngas. Date pits indicates high potential in maximising the hydrogen content in syngas. Abstract: Concerns related to global warming and the depletion of fossil fuels have propelled the global community to explore alternative renewable energy sources. Biomass is a nonconventional and renewable energy resource that can potentially be utilised for the production of sustainable heat and power. The thermal gasification process is an effective biomass conversion and utilisation method producing syngas as the product gas. This study details a biomass gasification process and subsequent optimisation, considering multiple parameters, including the type of feedstock and gasifying agent (gasifier) to maximise hydrogen production. Aspen Plus software is used to develop three agent-based biomass gasification models considering the characteristics of certain materials from Qatar built environment. The ultimate goal of the study is to optimise the gasification processes to yield different biomass blending options satisfying the maximisation of hydrogen generation through different scenarios. The capabilities of the built-in activated analysis package using Aspen Energy Analyser and Aspen Process Economic Analyser are utilised to evaluate the environmental and economic perspectives. The results demonstrate the excellence of steam-only biomass gasification in providing profitable and cleaner products. The yield of hydrogen production from blending of biomass feedstock achieved a high fraction of 5.23% with the steam-only gasification, while the yield increased from 1.63% to 5.22% for the oxygen/steam gasification when maximising the hydrogen fraction. Moreover, the selective limiting of biomass capacity enhances the quality of syngas through enriching the hydrogen production and lowers the need for subsequent adjustment and the manipulation of gasifying agent quantity and operating energy.